2003
DOI: 10.1590/s0004-282x2003000600019
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas depressivos e ansiedade em pacientes com cefaléia do tipo tensional crônica e episódica

Abstract: RESUMO -Introdução:A cefaléia do tipo tensional (CTT), dor cefálica mais comum, tem mecanismos fisiopatológicos, epidemiologia e apresentação clínica pouco estudados. Depressão e ansiedade são comorbidades especialmente enfocadas entre seus portadores. Objetivo: Estudar a ocorrência de sintomas depressivos e ansiedade entre portadores de CTT episódica (CTTE) e crônica (CTTC). Metodologia: Cinqüenta pacientes com CTTE e cinqüenta com CTTC preencheram os inventários de depressão e de ansiedade de Beck. Somente f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
4
0
8
Order By: Relevance
“…The evaluation of these disorders is frequently done using scales that only measure the clinical symptoms but do not diagnose the conditions 10,11 . However, this study evaluated the specificity and sensibility of the HAD scale for anxiety and depression using the M.I.N.I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of these disorders is frequently done using scales that only measure the clinical symptoms but do not diagnose the conditions 10,11 . However, this study evaluated the specificity and sensibility of the HAD scale for anxiety and depression using the M.I.N.I.…”
Section: Discussionmentioning
confidence: 99%
“…O objetivo deste estudo foi determinar a sensibilidade e a especificidade da Escala Hospitalar de Ansiedade e Depressão (HAD) em pacientes com dor crônica. , sendo freqüente que a avaliação desses distúrbios seja realizada por meio de escalas que medem apenas os sintomas clínicos e não realizam os diagnósticos 10,11 . Esse estudo, entretanto, avaliou a especificidade e a sensibilidade da escala HAD para ansiedade e depressão utilizando o M.I.N.I.…”
Section: Introductionunclassified
“…However, when the cause of painful phenomenon is not overcome, and it becomes a chronic process, feelings of hopelessness, impotence, and despair can turn into other depressive symptoms or the depression itself [25][26] . In this study, we observed an improvement in depressive symptoms in the group undergoing CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the responses obtained with the use of the HAD scale suggests that the high percentage of anxious and depressed patients may be due to the concomitance of these symptoms in patients with chronic pain 13 .…”
Section: Discussionmentioning
confidence: 99%